Caracterización social y económica de las experiencias exitosas de mujeres emprendedoras en el barrio Santa Helena de Villavicencio (Revista "Boletín el Conuco", 2020)
The concept of entrepreneurship as an object of study, contributes to the search for answers as to what being an entrepreneur or entrepreneurial and the connotation of this concept for different individuals of the society; in this sense was taken as reference theoretical Schumpeter to have a clearer definition of entrepreneurship, another relevant concept is gender, for this research has been taken the theory of Ritzer, which makes reference to the factors socialmacro and micro social that, in this case women are exposed by the gaps of generated that they exist in their different work. In this opportunity are you will give prominence to the woman, as subject active of experiences entrepreneurs, that contributes to the development social and economic of a context. The research is supported by a study of ethnographic character which aims to the interpretation of the context and the unit of analysis for the characterizationof socio-economic phenomena of female entrepreneurship, located in a territory and their interrelationships.
Keywords: entrepreneurship; gender; social factors; cohesion